An Analysis Of The English Textbook For Junior High School Vii Based On Content Standard Of BSNP - Rahma, Fahmawati Isnita; , Dra. Dwi Haryanti, M. Hum; , Siti Fatimah, S. Pd, M. Hum (2013)
This research is aimed at judging whether the content in the textbook entitled English in Focus for Grade VII Junior High School are appropriate with the content standard of BSNP or not. In this research, the writer uses qualitative research because the writer does not uses any number in analyzing the textbook. The object of this research is the English textbook entitled English in Focus for Grade VII Junior High School written by Artono Wardiman. The data is taken from the content in the English textbook. To collecting the data, the writer uses documentary method. Finally for analyzing data the writer presenting the content of the English textbook, analyzing the content of the English textbook with the content standard, judging the appropriateness content and matching the result with the schema of quality classification. After analyzing the textbook, the writer finds 10 competencies of content standard. And the percentage of the content in the English textbook is 100%. From the result, the writer concludes that based on the schema of quality classification, the content in English textbook entitled English in Focus for Grade VII Junior High School is appropriate with the content standard and it is very good to be used in the teaching learning process.